Efficient wage bargaining in a dynamic macroeconomic model - Volker Böhm; Oliver Claas (Bielefeld University, Institute of Mathematical Economics (IMW), 2012)
This paper analyzes the implications of bilateral bargaining over wages and employment between a producer and a union representing a finite number of identical workers in a monetary macroeconomic model of the AS
urn:nbn:de:0070-pub-26717353
Keywords: 330; AD type with government activity. Wages and aggregate employment levels are set according to an efficient (Nash) bargaining agreement while the commodity market is cleared in a competitive way. It is shown that; for each level of union power; measured by the share it obtains of the total production surplus; efficient bargaining implies no efficiency loss in production. Depending on the level of union power; temporary equilibria may exhibit voluntary overemployment or underemployment with the competitive equilibrium being a special case. Due to the price feedback from the commodity market and to income-induced demand effects; all temporary equilibria with a positive labor share are not Nash bargaining-efficient with respect to the set of feasible temporary equilibrium allocations. While higher union power induces a larger share of the surplus and a higher real wage; it always implies lower output and employment. Moreover; the induced nominal equilibrium wage is not always a monotonically increasing function of union power. Therefore; all temporary equilibria with efficient bargaining are only Second-best Pareto optimal; i.\; e. bargaining power and production efficiency do not lead to temporary optimality. The dynamic evolution of money balances; prices; and wages is analyzed being driven primarily by government budget deficits and expectations by consumers. It is shown that for each fixed level of union power; the features of the dynamics under perfect foresight are structurally identical to those of the same economy under competitive wage and price setting. These are: stationary equilibria with perfect foresight do not exist; except on a set of parameters of measure zero; balanced paths of monetary expansion or contraction are the only possibilities inducing constant allocations; for small levels of government demand; there exist two balanced paths generically; one of which with high employment and production is always unstable; while the other one may be stable or unstable.; Lohnverhandlungen; Beschäftigung; Wirtschaftliche Effizienz; Gewerkschaftsmitgliedschaft; Verhandlungsmacht; Spieltheorie; Makroökonomik; Dynamisches Modell; Theorie